2014
DOI: 10.4049/jimmunol.1302656
|View full text |Cite
|
Sign up to set email alerts
|

IL-27 in Human Secondary Lymphoid Organs Attracts Myeloid Dendritic Cells and Impairs HLA Class I–Restricted Antigen Presentation

Abstract: Different cytokines play crucial roles in inflammation and in polarizing immune responses, including IL-27 that exerts pro- and anti-inflammatory functions. Although the activity of IL-27 is well characterized in murine immune cells, only limited information is available regarding the natural cellular sources of IL-27 in humans and its effects on human immune cells. Dendritic cells (DCs) are the most potent professional APCs that in the immature state are positioned throughout peripheral tissues by acting as s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…In agreement with this literature, IL-27 has been shown to promote murine DC expression of CD39, which can deplete extracellular ATP and therefore limit inflammasome activation (156). In other studies, the ability of IL-27 to promote human DC expression of PD-L1 provides another mechanism for suppressing T cell activation (157), and there is evidence that IL-27 cripples the ability of DCs to present antigen (158). There have been reports that resting mouse macrophages are not responsive to IL-27 (159), but others have found that IL-27 inhibits the ability of murine macrophages to produce IL-12 and TNF-α (13).…”
Section: The Role Of Il-27 In Innate Responsesmentioning
confidence: 64%
“…In agreement with this literature, IL-27 has been shown to promote murine DC expression of CD39, which can deplete extracellular ATP and therefore limit inflammasome activation (156). In other studies, the ability of IL-27 to promote human DC expression of PD-L1 provides another mechanism for suppressing T cell activation (157), and there is evidence that IL-27 cripples the ability of DCs to present antigen (158). There have been reports that resting mouse macrophages are not responsive to IL-27 (159), but others have found that IL-27 inhibits the ability of murine macrophages to produce IL-12 and TNF-α (13).…”
Section: The Role Of Il-27 In Innate Responsesmentioning
confidence: 64%
“…Another potential cell candidate is dendritic cells (DCs). Human immature DCs exposed to IL-27 displayed reduced antigen presenting capacity 22 . IL-27 provokes DC derived IL-10, and suppresses downstream Th1 and Th17 response 20, 21 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the IL-27 receptor complex is also expressed on other immune cell types, including granulocytes 16 and macrophages 17 , indicating that the functional capabilities of IL27 may be even wider and in particular IL27 may play a role in mediating innate immunity. Indeed, IL-27 can impact the function of innate cell subsets, including macrophages 18 , neutrophils 16, 19 , and dendritic cells 2022 . It has been shown that IL-27 influences innate responses to bacterial challenge in the context of systemic sepsis in genetic manipulation models such as IL-27Rα knock-out murine strains.…”
Section: Introductionmentioning
confidence: 99%
“…) . While additional investigations are required to explore fully the wider biological functions of IL‐27, emerging data also highlight potential roles for IL‐27 in the control of pain , myeloid cell activation and stromal tissue responses (Fig. ) .…”
Section: The Inflammatory Significance Of Il‐6 and Il‐27mentioning
confidence: 99%